2010
DOI: 10.4137/jcd.s2822
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Regulates the Death ofM. tuberculosis-InfectedMacrophages

Abstract: Abstract:We previously described a caspase-independent death induced in macrophages by a high intracellular burden of Mycobacterium tuberculosis (Mtb). This death, with features of apoptosis and necrosis, releases viable bacilli for spreading infection. Interferon (IFN)-γ promotes survival of macrophages with a low intracellular Mtb load by inhibiting bacterial replication. Macrophages in naïve hosts are unable to restrict Mtb replication following aerosol transmission, but IFN-γ is increasingly present when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 37 publications
2
35
3
Order By: Relevance
“…Our conclusion that macrophage necrosis is induced by a high intracellular burden of H37Rv is consistent with several previous studies [4], [6], [30], [31], [32]. We speculate that although it may be possible to influence specific features of Mtb-induced cell death using inhibitors, as others have done [4], [6], [50], [51], cell death is an inevitable outcome in our infection model at MOI 10.…”
Section: Discussionsupporting
confidence: 93%
“…Our conclusion that macrophage necrosis is induced by a high intracellular burden of H37Rv is consistent with several previous studies [4], [6], [30], [31], [32]. We speculate that although it may be possible to influence specific features of Mtb-induced cell death using inhibitors, as others have done [4], [6], [50], [51], cell death is an inevitable outcome in our infection model at MOI 10.…”
Section: Discussionsupporting
confidence: 93%
“…Among factors contributing to these dynamics, we note that the survival of macrophages challenged with M. tuberculosis at MOI=1 in vitro is prolonged by IFN-γ activation, which prevents bacilli from growing to a burst size load [13]. We reported that IFN-γ exerts an opposite effect and accelerates necrosis of macrophages with a high intracellular bacillary load (MOI=25) [14]. This could explain the elimination of MPs containing >10 AFB at 24 weeks after infection with H37Ra which has limited or no replicative capacity at that late phase of TB disease and therefore does not continuously drive host cells to high AFB loads.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the reduction in IFNγ signaling may profoundly impair the ability of the host to check the replication of invading intracellular bacteria. IFNγ signaling can also rescue macrophages infected with low doses of Mtb from cell death [146], and stimulates hematopoiesis to repopulate depleted lymphocytes and neutrophils in infected tissues [147]. Thus, suppression of IFNγ signaling by type I IFNs could account for an increased presence of dying cells in tissues of infected mice.…”
Section: Discussionmentioning
confidence: 99%